(3QSGdI aj SH GdOjf hGdEjeGfs - (3YHO GdZfj Hf TGcQ Hf eMeO GdSGOGJ GdOeTbj GdMfaj,J (B1265 (3g` s ((3eMeO SYjO GdCSWhGfj SHW Gdefjfj GdMSjfj s)
(3ChdgG (B:s
(3hHYO aGdPj Gddg hGbVJg eJhf GdePgH hTQhMgG GdOjf Hge cajI edGc gPG GdTCf hRhLgG Cf GdQLd aj gPg GdMGOKI jYRQ hjDeQ HGdJhHI s
(3BNQgG (B:s
(3Cf JQSe HfTQ GdMRGe ai GdeMGeGJ Yf JcaQ Cgd GdESdGe HgG bjGe GdSGYI hSGYI GdbjGe NJGe GdSGYI hSGYI GdNJGe s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B274s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3Gdabg GdMfajs